2011
DOI: 10.1007/s10658-011-9866-3
|View full text |Cite
|
Sign up to set email alerts
|

Levels of fire blight (Erwinia amylovora) susceptibility of native apple, pear and quince germplasm from Lake Van Basin, Turkey

Abstract: Fire blight resistance of apple, pear and quince genetic resources from Lake Van Basin (eastern Turkey) was tested using Erwinia amylovora strain Ea Van. Shoot tips of 92 native accessions (48 accessions for apple, 38 accessions for pear and 6 accessions for quince) were wounded for inoculation, and artificially inoculated with pathogenic bacteria under greenhouse conditions. The levels of resistance of accessions were classified in comparison with control varieties according to the genotype susceptibility ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The choice of shoots for inoculation is also important. Fully vigorous shoots are more susceptible to disease, while shoots that grow weakly or those that have already completed growth are more resistant (Hepaksoy et al, 1999;Ozrenk et al, 2012). Harshman et al (2017) also noticed that the susceptibility of shoots to fire blight depends on their vigor and physiological condition.…”
mentioning
confidence: 99%
“…The choice of shoots for inoculation is also important. Fully vigorous shoots are more susceptible to disease, while shoots that grow weakly or those that have already completed growth are more resistant (Hepaksoy et al, 1999;Ozrenk et al, 2012). Harshman et al (2017) also noticed that the susceptibility of shoots to fire blight depends on their vigor and physiological condition.…”
mentioning
confidence: 99%
“…Among the hybrids, 1- 16-130, 1-17-20, 2-12-47, 2-15-33, 3-36-87, 2-12-43 and 2-15-93 showed very low susceptibility to fire blight, the most destructive disease for the pome fruit species, while the hybrid 2-15-42 showed low susceptibility, and the remaining hybrids showed high susceptibility (Table 3). It has been reported that cultivated pear varieties were highly susceptible to fire blight disease and suffer from great economic losses due to the disease (Hepaksoy et al, 1998;Ozrenk et al, 2012;Gaaliche et al, 2018). Therefore, breeding studies are carried out for the development of pear hybrids that are resistant to fire blight disease and have high fruit quality parameters (Evrenosoglu et al, 2010;Hunter, 2016;Evrenosoğlu and Mertoğlu, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it was stated that 'Kiefer' variety was resistant to blossom blight while moderately resistant to shoot blight; 'Conference' was moderately resistant to shoot blight but very susceptible to blossom blight; 'Santa Maria' and 'Williams' were susceptible to shoot blight and moderately susceptible to blossom blight (SOBICZEWSKI et al, 1997). As a result of similar researches, pears 'Williams' and 'Santa Maria' were determined to be susceptible to the disease, whereas 'Ankara', 'Mustafa Bey', 'Conference', and 'Kaiser Alexandre' were moderately susceptible, and 'Limon', 'Kiefer', and 'Magness' had low susceptibility (VAN DER ZWET and BEER, 1992; AYSAN et al, 1999;HEVESI et al, 2004;SESTRAS et al, 2008;OZRENK et al, 2012). As it can be understood from former studies in which the susceptibility of parental varieties to fire blight was investigated, s 'Ankara', 'Conference', 'Kaiser Alexandre', 'Kiefer' and 'Magness' were found to be relatively more resistant to the disease while 'Akca', 'Santa Maria' and 'Williams' were found to be susceptible.…”
Section: Discussionmentioning
confidence: 98%
“…Hybridization is generally used in breeding studies, due to the polygenic control of resistance to fire blight and complexity of its mechanism (BOKSZCZANIN et al, 2012). For this reason, studies have been carried out in many countries primarily on determining the susceptibility level of genetic resources for parent selection (HEVESI et al, 2004;HONTY et al, 2006;SESTRAS et al, 2008;OZRENK et al, 2012;KELLERHALS et al, 2012;TOTH et al, 2013;SOBICZEWSKI et al, 2015;CALIS et al, 2017;HARSHMAN et al, 2017;ŞAHIN et al, 2020).…”
Section: Introductionmentioning
confidence: 99%